Influence of Zostera marina L. and Z. noltei Hornem. (Zosterales: Liliopsida) on the composition, species richness and coenotic diversity of the phytobenthos of the Azov Sea - Afanasyev Dmitry (EDP Sciences, 2021)
The influence of marine higher plants Zostera marina and Z. noltei on the composition, species richness and coenotic diversity of the phytobenthos of sandy and silty soils of the Taman Bay in the Azov Sea at the depths from 0.5 to 3 m has been investigated. It is shown that 1) macrophytobenthic communities with a high degree of Z. noltei and Z. marina dominance (DD), both at very small and relatively large sites, are characterized by lower species richness than the communities with low DD; 2) that being said, for the majority of co-occurring species it is possible to grow in coenoses with any DD; 3) accordingly, about the same number of species can grow at the small community sites with low DD and at the larger sites with high DD; 4) DD has little to no influence on the species diversification of coenoses. However, both the growth of Zostera marina and Z. noltei and the decrease in their participation can lead to considerable drop in occurrence of some macroalgae species or to disappearance of those species from a community.